PERANCANGAN SIMULASI MEDIA PEMBELAJARAN DENGAN METODE DIVISION REMAINDER UNTUK PENCARIAN ALAMAT RELATIF PADA PROSES PENEMPATAN DATA - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2016)
Learning media is one medium that can help students understand the subject matter. No file system in the course material on how to put the data in a table. The material is the use of hashing technique in the search for the relative address of the data. In applying the hash function to find the relative address is probable some data have the same hash function results. This causes a collision (collision) at the time of placement data. Collision (collision) can be addressed by using multiple strategies, among others, Resolution Linear (Linear Resolution), and Double Hashing Overflow. The design of this simulation was organized which begins with the concept, design, material collecting, and assembly. At the design stage is divided into four stages, namely stages of the application process flowchart design, design app menu hierarchy, the design of the main menu display and design process flow aplikasi.Aplikasi calculation aims to assist lecturers in teaching so that students can easily understand and comprehend the material on the hash function particularly the division remainder method to find the relative address.